R. Chmel, Kompleks słowacki. Przeł. M. Bystzrak, T. Grabiński. Międzynarodowe Centrum Kultury. Kraków 2013, ss. 344. - Kuligowski, Waldemar (Porównania, 2014)
Rudolf Chmel, Kompleks słowacki. Przeł. M. Bystrzak, T. Grabiński. Międzynarodowe Centrum Kultury. Kraków 2013, ss. 344.